621 Robot-Assisted Radical Cystectomy: A Complete Audit Cycle of Our First 118 Cases. (12th October 2021) - Eli, N; Dowdeswell, M; Elsayed, W; Mak, D; Cooke, P
Abstract: Aim: There are 10, 200 cases of bladder cancer diagnosed every year in the UK, accounting for 3% of all new cancer diagnoses. Robot-assisted radical cystectomy (RARC) is a minimally invasive treatment option for muscle invasive and high-risk bladder cancer with a rising uptake. Between 2017 and 2019, RARC accounted for 40.6% of all cystectomies performed in the UK, increasing to 52% in 2018 to 2019. We compared our outcomes with the best practice of RARC set by the Pasadena consensus panel in 2015. Method: A review of the prospective database of all RARC performed by two surgeons at Royal Wolverhampton Hospital between May 2013 and October 2020 was conducted. Operative and oncological outcome data were collected from Clinical Web Portal and Somerset Cancer Register and analysed using Microsoft Excel. Results: A total of 118 RARC were performed in the study period, 50 cases were analysed in the first audit loop and 68 cases in the second. The mean age was 69 years (44 – 82), 84% were men and 70% were ASA grade II or less. Median operating time was 376 minutes (210 – 555) and the median blood loss was 250mls. 79% of urinary diversion was intra-corporeal and 84% was ileal conduit diversion. Median length of stay was 8 days; complication rate with Clavien Dindo score of III or higher was 12.7%. 86% of our patients are still alive. Conclusions: RARC is a safe option for the radical management of bladder cancer. Our outcomes are consistent with the Pasadena consensus recommendations.